Kaji Eksperimental Efek Kecepatan Sirkulasi Udara Dan Waktu Pembakaran Terhadap Performa Pembakaran Kompor Bio Massa - Muhamad Safii; Nur Hasim; Althesa Androva; Suheri Suheri (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
Indonesia is currently facing a significant challenge in managing its growing energy demands, driven by rapid population growth and accelerating economic development. This rising dependency on fossil-based fuels if left unaddressed poses serious environmental and social risks, including pollution, greenhouse gas emissions, and long-term energy insecurity. As a result, biomass has emerged as one of the most promising renewable energy alternatives, particularly for household and community cooking needs. This study investigates the combustion performance of biomass-based biopellets, formulated from a balanced blend of sawdust waste and rice bran, as the primary fuel source. Combustion experiments were carried out inside a purpose-built biomass stove with dimensions of 520 × 250 × 190 mm. To evaluate how airflow intensity and burning duration influence thermal output, three air velocity settings were applied 3 m/s, 6 m/s, and 9 m/s delivered through a controlled blower system. Combustion duration was systematically extended across ten intervals ranging from 60 seconds up to 600 seconds, allowing a detailed characterization of both combustion and thermal efficiency at each stage. Experimental results revealed that the highest thermal efficiency was consistently achieved at an air velocity of 9 m/s combined with a combustion duration of 600 seconds, yielding 46.349% for biopellets and 41.381% for wood. These figures demonstrate a clear positive relationship between increased airflow and prolonged burning time with overall energy conversion performance. The outcomes of this research are intended to serve as a practical engineering reference for designing next-generation biomass stoves that are both energy-efficient and environmentally responsible. Specifically, an air velocity of 9 m/s and a 600-second combustion window are strongly recommended as the benchmark operating parameters for optimal biomass stove performance in real-world applications.